2014
DOI: 10.1038/ncomms5407
|View full text |Cite
|
Sign up to set email alerts
|

Rab8a interacts directly with PI3Kγ to modulate TLR4-driven PI3K and mTOR signalling

Abstract: Toll-like receptor 4 (TLR4) is activated by bacterial lipopolysaccharide (LPS) to mount innate immune responses. The TLR4-induced release of pro-and anti-inflammatory cytokines generates robust inflammatory responses, which must then be restrained to avoid disease. New mechanisms for the critical regulation of TLR-induced cytokine responses are still emerging. Here we find TLR4 complexes localized in LPS-induced dorsal ruffles on the surface of macrophages. We discover that the small GTPase Rab8a is enriched i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
170
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(192 citation statements)
references
References 68 publications
(100 reference statements)
20
170
2
Order By: Relevance
“…Consequently, our novel findings of a beneficial effect of rapamycin on early stage of DN via TLR4 pathway in vivo, confirms a role of TLR4 in renal fibrosis, a dangerous factor of DN. Our findings also support Luo et al who suggest that TLR4-driven mTOR signaling plays a vital role in innate immune responses [39].…”
Section: Tlr-4supporting
confidence: 92%
“…Consequently, our novel findings of a beneficial effect of rapamycin on early stage of DN via TLR4 pathway in vivo, confirms a role of TLR4 in renal fibrosis, a dangerous factor of DN. Our findings also support Luo et al who suggest that TLR4-driven mTOR signaling plays a vital role in innate immune responses [39].…”
Section: Tlr-4supporting
confidence: 92%
“…Therefore, our findings show that, following CSF-1 receptor activation in macrophages, the majority of macropinocytic activity is derived from dorsal ruffles. This conclusion is consistent with an emerging view that the dorsal surface and ruffles might function as a membrane domain specialised for signalling (Abella et al, 2010;Luo et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Dorsal ruffles have a distinctive circular or curved upright architecture, are very dynamic and appear transiently following receptor activation. In some cells, dorsal ruffles are specialised for initiating receptor signalling (Abella et al, 2010;Luo et al, 2014), for example dorsal ruffles are abundant in macrophages following activation (Patel and Harrison, 2008;Yoshida et al, 2009). Although macropinocytosis has been linked to both peripheral ruffles and dorsal ruffles, some reports have suggested that peripheral ruffles might be more relevant than dorsal ruffles for initiating macropinocytosis (Buccione et al, 2004;Hoon et al, 2012;Suetsugu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…7). It was shown recently that MTs are required for targeting TLR4 to membrane ruffles following LPS activation (85). As stathmin overexpression also reduces membrane ruffles on macrophages, both the TLR4 signaling foci within these membrane structures as well as total surface TLR4 levels are impacted when stabilized MTs are diminished.…”
Section: Discussionmentioning
confidence: 98%